2013
DOI: 10.1097/jac.0b013e3182a12ea1
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory and Chronic Disease Care by Physician Assistants and Nurse Practitioners

Abstract: As the US population increases and ages, more patients require care. A reengineered health care system relies on physician assistants and nurse practitioners; however, the extent to which they care for medical conditions is marginally known. We analyzed ambulatory visits by provider type and diagnosis focusing on chronic diseases to identify differences in patients seen by each type of provider. Both physician assistants and nurse practitioners attended 14% of 777 million weighted visits. Overall, diabetes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…It has been estimated that up to 75% of rural primary care services could be provided by NPs and PAs (Doescher, Andrilla, Skillman, Morgan, & Kaplan, 2014;Sullivan-Marx, 2008). NPs and PAs are proportionately more likely to work in rural communities than are physicians (Grumbach, Hart, Mertz, Coffman, & Palazzo, 2003;Hooker, Benitez, Coplan, & Dehn, 2013;Hooker & Berlin, 2002) and, in many rural communities, an NP or PA serves as the only primary care provider (National Advisory Committee on Rural Health & Human Services, 2010). In addition, prior research has found that NPs and PAs are more likely than physicians to serve as providers of care for patients enrolled in Medicaid or paying for care out-of-pocket, particularly in rural areas (Benitez, Coplan, Dehn, & Hooker, 2015;Skillman, Fordyce, Yen, & Mounts, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that up to 75% of rural primary care services could be provided by NPs and PAs (Doescher, Andrilla, Skillman, Morgan, & Kaplan, 2014;Sullivan-Marx, 2008). NPs and PAs are proportionately more likely to work in rural communities than are physicians (Grumbach, Hart, Mertz, Coffman, & Palazzo, 2003;Hooker, Benitez, Coplan, & Dehn, 2013;Hooker & Berlin, 2002) and, in many rural communities, an NP or PA serves as the only primary care provider (National Advisory Committee on Rural Health & Human Services, 2010). In addition, prior research has found that NPs and PAs are more likely than physicians to serve as providers of care for patients enrolled in Medicaid or paying for care out-of-pocket, particularly in rural areas (Benitez, Coplan, Dehn, & Hooker, 2015;Skillman, Fordyce, Yen, & Mounts, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In collaboration with physician colleagues, PAs have expanded into nearly all areas of medicine; PAs increase access to primary care, are more likely than physicians to practice in rural, underserved areas, and are generally more satisfi ed with career choice than physicians. 22,25,26,28 The profession has made great strides in a short period of time due to the efforts of both men and women and, in general, women are as satisfi ed with the career choice of PA as men. 21,25 Unlike men, however, women cite issues related to respect as the most dissatisfying aspect of their careers.…”
Section: Discussionmentioning
confidence: 99%
“…This is half the percentage of ambulatory care visits for chronic diseases managed by PAs and NPs in similar studies. 23 This suggests that PAs and NPs may be underutilized in the care of individuals with depression. Increasing visits for adults with depression managed by PAs and NPs could increase access to care, which may help to increase healthcare system efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In the NHAMCS, the clinic is the destination of the patient and, thus, the visit is attributed to the clinician providing the service. 21,23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation